Transparency and Trust in Minahasa Tourism Advertising using Blockchain - Rianto, Indra; Djamen, Arje Cerullo; Tampi, Tesalonika Inryanti; Langitan, Jentelino Silvester; Modeong, Merriam (CogITo Smart Journal, 2025)
Abstract Tourism plays a vital role in driving economic growth, and Minahasa holds strong potential to optimize this sector. However, challenges remain in digital advertising, particularly regarding transparency and consumer trust. This study investigates the impact of blockchain technology on transparency, trust, and the effectiveness of digital advertising in Minahasa’s tourism industry. A quantitative explanatory design was employed using Partial Least Squares Structural Equation Modeling (SEM-PLS), with data collected from 150–250 respondents through purposive and snowball sampling techniques.The findings reveal that blockchain significantly influences all key variables. It enhances advertising transparency (T-statistic = 36.738, p = 0.000), strengthens consumer trust (T-statistic = 33.164, p = 0.000), and improves advertising effectiveness (T-statistic = 28.400, p = 0.000). These results highlight blockchain’s capacity to provide immutable records, ensure data authenticity, and optimize ad performance through verifiable real-time information. This study confirms that blockchain can serve as a strategic tool to promote transparent, trustworthy, and effective digital advertising in tourism. The findings provide practical insights for tourism stakeholders and contribute to academic discussions on technology-driven marketing innovation.